Eksplorasi Faktor Risiko Penyakit Kardiovaskular dan Hubungannya dengan Kejadian Hipertensi pada Guru Biologi di Gorontalo - Antonius Yansen Suryadarma; Nathania Disa Ariesta Andriani; Minarni Wartiningsih; Cempaka Harsa Sekarputri; Edwin Hadinata (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Background: Cardiovascular disease (CVD) remains the foremost cause of mortality worldwide, with hypertension being the most important modifiable risk factor. Although teachers play an important role in health education, evidence on CVD risk factors among teachers, particularly biology teachers, remains limited. This study aimed to describe CVD risk factors and explore their association with hypertension among biology teachers in Gorontalo. Methods: A cross-sectional study was conducted among 39 members of the Musyawarah Guru Mata Pelajaran (MGMP) biology teacher in Gorontalo City. Data were collected through questionnaires and physical examinations. Association between categorical variables were analyzed using the Chi-square / Fisher's exact test, along with odds ratios (OR) and 95% confidence intervals (CI). Results: Most participants were female (87.2%) and aged ≥40 years (66.7%). The prevalence of hypertension, overweight/obesity, and central obesity was 59.0%, 61.5%, and 71.8%, respectively. Insufficient physical activity was identified in 43.6% of participants, while daily consumption of sweet foods, sugar-sweetened beverages, and monosodium glutamate (MSG) seasonings remained common. Bivariate analyses showed no significant association between investigated risk factors and hypertension. However, a higher risk of hypertension was observed among those aged ≥40 years (OR = 3.60; 95% CI: 0.73–18.41) and those with mental health problems, although the associations were not statistically significant. Conclusion: Biology teachers in Gorontalo had a high burden of CVD risk factors, particularly hypertension, overweight/obesity, central obesity, and unhealthy dietary habits. These findings support strengthening health promotion, routine screening, and implementing the GERMAS and CERDIK programs in schools to prevent CVD.